Investigation of The Effect of Smoking on Some Blood Parameters and Respiratory Functions in Wrestlers - Kürşat Hazar (Selcuk University, 2019)
ABSTRACT This study was conducted to investigate the effects of smoking on some blood parameters and respiratory functions in wrestlers. To the study 18 non-smoker wrestling athletes for at least 11 ± 500 years, studying at different departments at Muğla Sıtkı Koçman University Faculty of Sport Sciences, whose average age 20 ± 888, average height 177 ± 555, average weight 82 ± 777 kg; and 16 athletes smoking 15± 062 pieces of cigarettes in a day for averagely 3 ± 406 years, doing licenced wrestling at least for 11 ± 625 years whose average age 22 ± 000, height average 179 ± 375, weight average 86 ± 250; a total of 34 male individuals voluntarily participated in the study. Height and body weight measurements, blood analysis and pulmonary function tests were respectively applied to the participants. Statistical analysis of the obtained data was done by SPSS 21.00 package program. Since the data were distributed normally, the Independent-Samples T Test was used for intergroup comparisons, and the level of significance was set at p lt;0.05 and 0.01 by using regression analysis test methods. RBC values of the smokers were significantly higher than the ones who did not (p lt;0.01), and the results of the respiratory function test showed that there were significant differences in favor of the non-smokers (p lt;0.01, p lt;0.05). While RBC and HGB values of cigarette users were found to be significantly higher, non-smokers had a 35.2% effect on RBC values of 33.9%, while FVC and FEF25 / 75 were significantly lower than non-smokers. FVC values of -47.4%, and FEF25 / 75 were found to have an effect of -65.7%. In conclusion, it was determined that smoking in wrestlers has statistically significant but negative effects on some blood parameters and respiratory functions. For this reason, it is necessary to emphasize the importance of smoking in the wrestlers to ensure that both athletes and coaches demonstrate the required sensitivity.